Guidance of regulatory T cell development by Satb1-dependent super-enhancer establishment - Kitagawa, Yohko (Nat Immunol, 2016)
Most Foxp3(+) regulatory T (T(reg)) cells develop in the thymus as a functionally mature T cell subpopulation specialized for immune suppression. Their cell fate appears to be determined before Foxp3 expression; yet molecular events that prime Foxp3(−) T(reg) precursor cells are largely obscure. We found that T(reg) cell–specific super-enhancers (T(reg)-SEs), which were associated with Foxp3 and other T(reg) cell signature genes, began to be activated in T(reg) precursor cells. T cell–specific deficiency of the genome organizer Satb1 impaired T(reg)-SE activation and the subsequent expression of T(reg) signature genes, causing severe autoimmunity due to T(reg) cell deficiency. These results suggest that Satb1-dependent T(reg)-SE activation is crucial for T(reg) cell lineage specification in the thymus and that its perturbation is causative of autoimmune and other immunological diseases.